Intermediates of Bacteriophage MS2 Assembly In Vivo - Bonner, Philip H. (1974)
The in vivo process of virion assembly was studied in rifampin-treated, MS2-infected Escherichia coli during late times of infection—after 18 min postinfection. Differential sucrose gradient sedimentation of infected-cell lysates taken at various times after radioactive labeling indicated a definite temporal order of appearance of phage-specific protein in assembly-related structures. Labeled MS2 protein appears first as a low-molecular-weight peak at the tops of gradients, then as a peak at 40S and as a large number of almost unseparable structures between 40 and 80S, and finally as 80S mature phage particles. During the chase of a short labeling period, radioactive phage protein was found to disappear from gradients in the same temporal order as it appeared; the soluble peak disappears first, followed by the 40 to 70S region. The chased label appears quantitatively in the 80S phage peak. Labeled phage RNA was found to appear first in the 40S peak, then in the structures between 40 and 70S, and finally in 80S phage particles. The order of disappearance of labeled phage RNA during a chase is the same as its appearance. Resedimentation of the 40 to 70S region indicated the presence of distinct structures at 60 and 70S and many indistinct ones between 40 and 60S. The smaller intermediates exhibit separable maturation protein-rich and coat protein-rich segments, indicating nonrandom binding of the two proteins during the initial steps of assembly. Larger, discrete intermediates appear at 60 and 70S. Treatment of the various structures with pancreatic RNase results in destruction of those from 40 through 60S; treatment of the 70S structure results in the conversion of some of it to a 45S peak, presumably the complete capsid. A small fraction of the 80S phage peak is also sensitive to RNase, resulting in a similar 45S peak. Pulse-chase experiments indicate that structures from 40 through 60S as well as the RNase-sensitive 70S structure are assembly intermediates, but that the RNase-insensitive 70S and the RNase-sensitive 80S structures are not.